EXPLORATION OF BUGIS ORAL LITERATURE "MEONGPALO KARELLAE" IN THE MASSUREK TRADITION: A STUDY OF THE MADDOJA BINE TRADITION IN MAROS - Amin, Kasma F; Amin, Nurtaqwa; Chuzaimah; Hamsiah, Andi; Bazergan, Emma (Prosiding Konferensi Internasional Kesusasteraan, 2025)
Meong Palo Karellae is a Bugis ethnic oral literature that forms part of the ancient epic I La Galigo. This folklore narrates the origin of rice, which is usually performed during the planting season ritual. This study is important for preserving old literary heritage that embodies local wisdom, so that the younger generation has references for building strong character. The method used is descriptive qualitative with a hermeneutic theoretical approach. The steps include preparing the story text, collecting data, analysis, interpretation, and data triangulation. The exploration results show that the oral literature Meong Palo Karellae demonstrates forms of adaptation, pattern change, integration, and latency. The good character traits found in Meong Palo Karellae include: (1) helpfulness, (2) care, (3) respect for guests, (4) tolerance, (5) environmental preservation, (6) loyalty, and (7) steadfastness in principles. The negative traits include: (1) stinginess, (2) selfishness, (3) greed, and (4) anger. Oral literature serves as a bridge between the past and the present, teaching the younger generation about local wisdom that remains relevant in responding to contemporary challenges.